Challenges of Online Learning and Attitude of Medical Student at LUMHS: Comparative Study among Rural and Urban Students during Covid -19 Pandemic (Medical Forum Monthly, 2021)
Objective: To enumerate the challenges of online learning faced by urban and rural medical students in LUMHS and highlight the preference of medical students regarding online learning also seek association of medical students of both populations with the challenges of online learning.Study Design: A comparative Cross sectional studyPlace and Duration of Study: This study was conducted at the Liaquat University of Medical and Health Sciences, Jamshoro from February 2021 to April, 2021.Materials and Methods: This study was conducted among urban and rural MBBS students of LUMHS, via non probability convenient sampling. A predesigned close ended Google form questionnaire used to gather data. The data was analyzed by using SPSS 23.00 with significant p< 0.05. Students who were willing to participate are included in the study while who were not willing to participate were excluded.Results: Among 487 students of LUMHS 43.7% male and 56.3% female. 55.3% to urban areas and 44.9% to rural areas. 89.52% of students have internet availability. 69.02% of urban and 82.64% of rural population shows problem of internet signals.82.08% of urban and 91.78% rural students faced electricity problem. 78.85% of respondents said their study work increased due to e-learning and 52.15% faced problem of privacy. 62.68% and 76.86% of urban while 76.25% and 81.27% of rural students feels stress on submission of assignment and appearing in online test/ exams. Most of 86.19% of urban and 85.84% of rural didn’t prefer online teaching. while76.86% urban and 75.34% rural student said online teaching should not be made part of regular education.Conclusion: Students of both population were facing problems of internet, electricity, privacy of learning and feel stress during online submission of assignment and test/exams. Students belongs to urban population was facing less problem of internet and electricity than rural students (p<0.001).